2021
DOI: 10.3390/polym13132127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Combination of Levofloxacin with Cationic Carbosilane Dendron and Peptide in the Prevention and Treatment of Staphylococcus aureus Biofilms

Abstract: Antibiotic resistance and biofilm-related infections, persistent in conventional antimicrobial treatment, are continuously increasing and represent a major health problem worldwide. Therefore, the development of new effective treatments to prevent and treat biofilm-related infections represents a crucial challenge. Unfortunately, the extensive use of antibiotics has led to an increase of resistant bacteria with the subsequent loss of effectivity of commercial antibiotics, mainly due to antibiotic resistance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Scanning electron microscopy (SEM) was performed to evaluate morphological changes in P. aeruginosa cell wall after treatment with dendrimers in TSB at 37 • C for 24 h. The samples for SEM were prepared following the methodology previously described [43,44]. Critical-point drying was carried out with a Polaron CPD7501 critical-point drying system and sputter coated with 200 Å gold-palladium using a Polaron E5400.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Scanning electron microscopy (SEM) was performed to evaluate morphological changes in P. aeruginosa cell wall after treatment with dendrimers in TSB at 37 • C for 24 h. The samples for SEM were prepared following the methodology previously described [43,44]. Critical-point drying was carried out with a Polaron CPD7501 critical-point drying system and sputter coated with 200 Å gold-palladium using a Polaron E5400.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Therefore, we would be missing tremendously relevant information and we would be giving inaccurate information. However, studies carried out with the resazurin method have shown good efficacy and reliable and complete results [19][20][21][22]. Resazurin does not require additives or dissolve salts with DMSO, as is the case with the dyes mentioned above (Figure 1).…”
Section: Determination Of the Viability Of A Candida Biofilm In Vitromentioning
confidence: 99%
“…The use of these dendritic systems has been studied in both gram-negative and gram-positive bacteria [28][29][30][31], including planktonic phase and biofilms [20,22,32,33]. Its efficacy has also been evaluated in eukaryotes, such as yeasts (Candida spp.)…”
Section: Dendritic Cationic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides containing arginines and tryptophans were bound to dendrimers and tested against planktonic persister cells, regular planktonic cells and persister cells in preformed E. coli biofilmst [131,132]. A cationic carbosilane dendrimer functionalized with an antibiotic and a peptide was developed to inhibit the formation of S. aureus biofilms, showing both antibiofilm-damaging and -inhibitory activities [133].…”
Section: Nv Potential Against Biofilmsmentioning
confidence: 99%